Microsoft Dynamics CRM unleashed - Wolenik, Marc J. (Sams, 2014)
Microsoft® Dynamics CRM 2013 Unleashed presents start-to-finish guidance for planning, customizing, deploying, integrating, managing, and securing both cloud and on-premise based versions of Dynamics CRM. Leading Dynamics implementer Marc Wolenik fully covers Microsoft Dynamics CRM 2013, Microsoft Dynamics CRM Online Fall '13, and many features first introduced in Microsoft's "Polaris" and Update Rollup 12. You'll find thorough coverage of Dynamics' revamped "Flow" interface and advanced cross-platform mobile client support. Extensive new coverage also includes: Business Process Flows, Portable Business Logic, reporting and forms improvements, server-side email synchronization, MarketingPilot, NetBreeze, Yammer, and much more. Drawing on extensive insider knowledge, Wolenik presents proven best practices and pitfalls to avoid in using every significant Dynamics CRM 2013 capability- information available in no other book . Marc J. Wolenik, is CEO of Webfortis, a Microsoft Gold Customer Relationship Management Competency Partner that specializes in delivering Microsoft Dynamics CRM/xRM solutions for companies of all sizes. Learn from experience and dive deep into CRM technologies that cross almost every industry and vertical. His books include Microsoft Dynamics CRM 2011 Unleashed, Microsoft CRM 4 Unleashed, and Microsoft CRM 4 Integration Unleashed . Detailed information on how to ... Compare on-premise and cloud versions of Dynamics CRM, make your best choice, and deploy painlessly Use the advanced configuration and customization options that offer you the most value Take full advantage of Dynamics CRM's new flow interface and productivity shortcuts Learn about new add-on features for Dynamics, including MarketingPilot, NetBreeze, and Yammer Personalize dashboards, activities, calendars, data import/export, and more Manage leads, opportunities, accounts, contacts, marketing lists, collateral, campaigns, quotes, orders, and invoices Integrate schedules, cases, contacts, and product/service information Build powerful automated workflows, processes, and complete solutions Deliver CRM applications to smartphones and tablets, including iOS devices Provide watch lists, automatic alerts, and other sales help through InsideView Social Insights Extend Dynamics CRM with custom plug-ins and add-ons Integrate Dynamics CRM 2013 with SharePoint, Azure, SQL Server, SRSS, Visual Studio, and .NET Framework ON THE WEB: Download all examples and source code prese ...